Anaerobic expression of the gadE-mdtEF multidrug efflux operon is primarily regulated by the two-component system ArcBA through antagonizing the H-NS mediated repression - Deng, Ziqing; Shan, Yue; Pan, Qing; Gao, Xiang; Yan, Aixin (Frontiers in Microbiology, 2013)
The gadE-mdtEF operon encodes a central acid resistance regulator GadE and two multidrug efflux proteins MdtEF. Although transcriptional regulation of gadE in the context of acid resistance under the aerobic growth environment of Escherichia coli has been extensively studied, regulation of the operon under the physiologically relevant environment of anaerobic growth and its effect on the expression of the multidrug efflux proteins MdtEF in the operon has not been disclosed. Our previous study revealed that anaerobic induction of the operon was dependent on ArcA, the response regulator of the ArcBA two-component system, in the M9 glucose minimal medium. However, the detailed regulatory mechanism remains unknown. In this study, we showed that anaerobic activation of mdtEF was driven by the 798 bp unusually long gadE promoter. Deletion of evgA, ydeO, rpoS, and gadX which has been shown to activate the gadE expression during acid stresses under aerobic condition did not have a significant effect on the anaerobic activation of the operon. Rather, anaerobic activation of the operon was largely dependent on the global regulator ArcA and a GTPase MnmE. Under aerobic condition, transcription of gadE was repressed by the global DNA silencer H-NS in M9 minimal medium. Interestingly, under anaerobic condition, while ΔarcA almost completely abolished transcription of gadE-mdtEF, further deletion of hns in ΔarcA mutant restored the transcription of the full-length PgadE-lacZ, and P1- and P3-lacZ fusions, suggesting an antagonistic effect of ArcA on the H-NS mediated repression. Taken together, we conclude that the anaerobic activation of the gadE-mdtEF was primarily mediated by the two-component system ArcBA through antagonizing the H-NS mediated repression.